Reduced p.p.-rings without identity - Xiaojiang Guo; K. P. Shum (International Journal of Mathematics and Mathematical Sciences, 2006)
We give some necessary and sufficient conditions for p.p.-rings without identity to be reduced. Our results strengthen and extend the results of Fraser and Nicholson as well as some recent results we obtained on reduced p.p.-rings with identity.